Manna from heaven for judges: Judges' reaction to a quasi-random reduction in caseload - Christoph Engel; Keren Weinshall (Max Planck Institute for Research on Collective Goods, 2020)
What is the impact of caseload on judicial decision-making? Is increasing judicial staff effective in improving judicial services? To address these questions, we exploit a natural, near-randomized experiment in the Israeli judiciary. In 2012, six senior registrars were appointed in two of the six magistrate's court districts. The choice of districts was motivated by reasons unrelated to judicial performance. In these two districts, the civil caseload per judge was substantially reduced. We find that the reduction had a significant impact on the process and outcomes of judicial decision-making. Judges working in courts with reduced caseload invested more resources in resolving each case. The effect is mostly to the advantage of plaintiffs, who were more likely to win, recover a larger fraction of their claim, and be reimbursed for litigation costs. We discuss the implications for judicial management and theories about judicial decision-making.
hdl:21.11116/0000-0005-80D5-9
Keywords: D02; D21; D22; D83; K10; K41; 330; Rechtsberufe; Entscheidung; Arbeitsintensität; Dienstleistungsqualität; Israel